Determinants of the Probability of Non-repayment of Loans Granted to Individuals - Calin, Ana Maria; Pargaru, Oana Iacob; Raducan, Dragos; Buzoianu, Ovidiu Andrei Cristian (European Journal of Sustainable Development, 2023)
This paper presents non-performing loans granted to individuals as well as methods of prevention and recovery. This risk of non-repayment is recorded when the debtor cannot honor his due obligations to the bank in time according to the credit agreement. The objectives of the homework are to understand the credit system of natural persons, to know and carefully analyze the client's file with the aim of making or not the credit decision and finally granting the loan. Credit restructuring is an essential method in counteracting the appearance of non-performing loans, which aims to support a bank's customers, so that they can deal with financial impasse situations that have temporarily arisen in the various stages of the development of credit contracts. The process of periodic verification of the contract with the borrower, the guarantees offered, including visits to the place where the client operates are essential factors in order to prevent the risk of default. Loans approved for borrowers who, during the course of the lending period, experience a worsening economic-financial situation are called non-performing loans, that is, they can no longer meet the terms of repayment of the loan, nor can they cover the interest expense and related commissions. Key words: bank, COVID-19, credit, loans